Effect of Flavonoids in Hawthorn and Vitamin C Prevents Hypertension in Rats Induced by Heat Exposure - Wei Du; Hong-Min Fan; Yu-Xin Zhang; Xiao-Hua Jiang; Yun Li (Molecules, 2022)
Background: Excessive oxidative stress is associated with hypertension in professional high-temperature working conditions. Polyphenols exhibit a cardioprotective effect. Hawthorn contains high amounts of flavonoids, though its effect on hypertension protection has yet to be studied. This study aims to investigate this effect of extract of hawthorn (EH) or its combination with vitamin C (Vit. C) in rats induced by working under a hot environment. Methods: Forty-two male rats were randomly divided into a control group under normal temperature and six treatment groups exposed at 33 ± 1 °C along with 1 h of daily treadmill running. They were orally provided with water, Vit. C (14mg/kg), EH (125, 250, and 500 mg/kg), and EH500 + Vit. C, once a day for four weeks. Results: Both EH and Vit. C alone reduced the systolic and diastolic blood pressure of rats exposed to the heat environment; however, their joint supplementation completely maintained their blood pressure to the normal level throughout the experimental period. No morphological changes were found on the intima of aorta. Moreover, the co-supplementation of EH and Vit. C prevented the changes of heat exposure in inducing oxidative stress markers, such as glutathione peroxidase, catalase, total antioxidant capacity, and nitric oxide; the synergistic action was more effective than either individual treatment of EH and Vit. C. Furthermore, the administration of EH had more potent effects on increasing superoxide dismutase, IL-2, the 70 kilodalton heat shock proteins and high sensitivity C reactive protein, and decreasing serum malondialdehyde and lipofuscin in vascular tissue than those in Vit. C group. Conclusions: A strong synergistic effect of EH and Vit. C on the prevention of hypertension under heat exposure was established, as they inhibited the oxidative stress state. This study also sets up a novel intervention strategy in animal models for investigation on the early phases of hypertension induced by heat exposure.